Extreme issues related to irrational functions and geometric methods for solving equations - Akhmedova Gavkhar Akhadovna; Makhmudova Ozoda Yuldashevna (International Journal on Orange Technologies, 2021)
We all know that there are several algebraic ways to solve irrational equations and extreme problems. Solving examples and problems in geometric ways helps to increase students' interest in mathematics and to see more clearly the relationship between geometry and algebra. In this article, a triangle area is used to solve an irrational equation, the cosine theorem, and vectors are used to solve extreme problems.